KEPEMIMPINAN PEREMPUAN (Kajian Strategis Kepemimpinan Berbasis Gender) - Suyatno (MUWAZAH : jurnal kajian gender, 2014)
Terms of women's emancipation or gender equality is often touted in almost all corners of the world, able to open a general idea to rethink creature named women to become leaders, even heads of state. The discussion will be more interesting when the position of women in the social facts are also removed. It is of course behind the reconstruction of the position of women in the historical and political arena. Both studies and evidence from the Quran, the Hadith, and the explanation of the experts in the field, shows that women do not experience gender barriers to explore her potential and release energy to become a leader in the community when the community around it has not considered taboo and acknowledged benefits. In addition, the permissibility of being a leader must also be supported by personal qualities include: ability, capacity, faculty, and skills.